AT&T quality improvement cycle - Coleman, Roberta...[et al] (AT&T Bell Laboratories Pub. Center [S.l.]US, 1998)
Offers a proven system of specific activities designed to assist quality improvement teams in identifying, defining, and resolving process problems. Proposes methodology, supported by a package of tools and techniques, that will facilitate problem analysis and promote teamwork. Includes the AT&T quality policy, and provides a glossary.